2014
DOI: 10.3906/kim-1405-43
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical and spectroelectrochemical characterization of chloromanganese(III) phthalocyanines

Abstract: pentoxy-benzyloxy units is reported. The new compounds have been characterized by using elemental analyses and UV-Vis, FT-IR, and mass spectroscopic data. The electrochemical properties of the manganese phthalocyanine complexes were investigated by cyclic and square wave voltammetry and the nature of the observed redox processes was studied by spectroelectrochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Fluorescence emission peak of 5 was detected at 705 nm and Stokes' shifts was evaluated as 27 nm. The observed Stokes' shift was within the region ∼20-30 nm as typical for Pc complexes (46). The excitation spectrum was similar to absorption spectrum and both were mirror images of the fluorescent spectra for 5 in DMF.…”
Section: Synthesis and Spectroscopic Characterizationsupporting
confidence: 65%
“…Fluorescence emission peak of 5 was detected at 705 nm and Stokes' shifts was evaluated as 27 nm. The observed Stokes' shift was within the region ∼20-30 nm as typical for Pc complexes (46). The excitation spectrum was similar to absorption spectrum and both were mirror images of the fluorescent spectra for 5 in DMF.…”
Section: Synthesis and Spectroscopic Characterizationsupporting
confidence: 65%
“…As expected, H 2 Pc with D 2 h symmetry was confirmed by two absorption bands in the visible region (685 and 713 nm). [ 49–51 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, many potent phthalocyanines are hydrophobic and are poorly soluble in water [37]. Studies have shown that solubility of phthalocyanine plays a major role in determining its electrochemical, chemical, and physical properties [9,12].…”
Section: Applications Of Phthalocyaninementioning
confidence: 99%